Neurologic urinary incontinence - Wyndaele J. (2017)
Introduction: This manuscript summarizes the work of Committee 10 on neurologic bladder and bowel of the International Consultation on Incontinence in 2008-2009. As the data are very large the outcome is presented in different manuscripts. This manuscript deals with neurologic urinary incontinence. Methods: Through in debt literature review all aspects of neurological urinary incontinence were studied for levels of evidence. Recommendations for diagnosis and treatment, and for future research were made. Results: Pathophysiology was summarized for different levels of lesions. For epidemiology, specific diagnostics, conservative treatment and surgical treatment of neurologic urinary incontinence, levels of evidence and grades of recommendation were made following ICUD criteria. Conclusions: Though data are available that advice and guide in the management of urinary incontinence in neurologic patients, not many data have a high level of evidence or permit a high grade of recommendation. More and well-structured research is needed. © 2009 Wiley-Liss, Inc.